Prevalence of low anterior resection syndrome and impact on quality of life after rectal cancer surgery: population‐based study. Issue 5 (12th June 2020) - Pieniowski, E. H. A.; Nordenvall, C.; Palmer, G.; Johar, A.; Tumlin Ekelund, S.; Lagergren, P.; Abraham‐Nordling, M.
Abstract : Background: The prevalence of major low anterior resection syndrome (LARS) after rectal cancer surgery varies from 17·8 to 56·0 per cent, but data from high‐quality studies are sparse. The aim of this study was to determine the prevalence of LARS and its association with quality of life (QoL) in a large, well defined, population‐based cohort. Methods: This was a population‐based study that included all patients who had curative rectal cancer surgery with total or partial mesorectal excision in Stockholm County in Sweden between 2007 and 2013. Patients without a remaining stoma, free from cancer and alive in April 2017 were eligible for the study. The LARS score questionnaire, EORTC QLQ‐C30 and Cleveland Clinic Florida Fecal Incontinence score were used as outcome measures. Adjusted mean scores (and differences) of EORTC QLQ‐C30 for LARS groups were calculated using repeated measures ANCOVA regression models while adjusting for predefined confounders. Results: In total, 481 patients (82·6 per cent response rate) were included in the analysis. Mean follow‐up time was 6·7 (range 3·4–11·0) years after surgery. The prevalence of LARS was 77·4 per cent (370 of 478 patients), with 53·1 per cent (254 of 478) experiencing major LARS. Patients with major LARS reported worse on all EORTC QLQ‐C30 subscales (except for financial difficulties) than patients without LARS. A higher mean LARS score was associated with a greater impact on bowel‐related QoL. Conclusion: After anterior resection for rectal cancer, the majority of patients suffer from major LARS with a negative impact on QoL. Abstract : A consequence of rectal cancer surgery is bowel dysfunction, also known as low anterior resection syndrome (LARS). In this cross‐sectional study, the prevalence of major LARS was 53·1 per cent. Major LARS was associated with a greater impact on bowel‐related quality of life. Very common with significant impact on quality of life Abstract : Antecedentes: La prevalencia del síndrome de resección anterior baja ( Low Anterior Resection Syndrome, LARS) mayor después de cirugía del cáncer de recto varía entre 17, 8% y 56, 0%, pero los datos procedentes de estudios de alta calidad son escasos. El objetivo de este estudio fue determinar la prevalencia de LARS y su asociación con la calidad de vida ( quality of life, QoL) en una gran cohorte poblacional bien definida. Métodos: Este fue un estudio de base poblacional con todos los pacientes que se sometieron a cirugía curativa de cáncer de recto con exéresis total o parcial del mesorrecto en el condado de Estocolmo en Suecia entre 2007‐2013. Los pacientes sin estoma definitivo, sin recidiva y vivos en abril de 2017 fueron elegibles para el estudio. El cuestionario de puntuación LARS, el EORTC QLQ‐C30 y el sistema de puntuación de incontinencia de la Cleveland Clinic Florida se usaron como medidas de resultado. Las puntuaciones medias ajustadas (y las diferencias) de EORTC QLQ‐C30 para grupos LARS se calcularon utilizando modelos de regresión ANCOVA de medidas repetidas ajustando por factores de confusión predefinidos. Resultados: En total, 481 pacientes (tasa de respuesta del 82, 6%) se incluyeron en el análisis. El tiempo medio de seguimiento fue de 6, 7 años después de la cirugía (rango 3, 4‐11, 0 años). La prevalencia de LARS fue 77, 4% ( n = 370) y un 53, 1% ( n = 254) presentó un LARS mayor. Los pacientes con LARS mayor tuvieron peores resultados en todas las subescalas EORTC QLQ‐C30 (excepto por dificultades financieras) que los pacientes sin LARS. Una puntuación LARS media más alta se asoció con un mayor impacto en la calidad de vida relacionada con el intestino. Conclusión: Después de una resección anterior por cáncer de recto, la mayoría de los pacientes sufren un LARS mayor con un impacto negativo en la calidad de vida.